2017
DOI: 10.1007/s10916-017-0725-4
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Three-Dimensional Tools to Learn Anatomy

Abstract: We present a new generation tool based of interactive 3D models. This models are based on the radiological two-dimensional images by computed tomography imaging. Our article focuses on the anatomical region of the skull base. These new three-dimensional models offer a wide field of application in the learning, as they offer multiple visualization tools (rotation, scrolling, zoom…). In this way, understanding of the anatomical region is facilitated. A feature to be dismissed is that a professional workstation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Of the total 200 articles, the simple possibility of using 3D PDF (without providing further details) was mentioned in 13 articles (6.5%) [ 27 - 39 ]. Another 18 (9.0%) [ 2 , 3 , 23 , 40 - 54 ] articles described a way, method, or idea how to use or to utilize 3D PDF technology and 19 articles (9.5%) [ 20 , 40 , 55 - 71 ] described a method, protocol, software, library, or other means for the creation of 3D PDFs or model files.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the total 200 articles, the simple possibility of using 3D PDF (without providing further details) was mentioned in 13 articles (6.5%) [ 27 - 39 ]. Another 18 (9.0%) [ 2 , 3 , 23 , 40 - 54 ] articles described a way, method, or idea how to use or to utilize 3D PDF technology and 19 articles (9.5%) [ 20 , 40 , 55 - 71 ] described a method, protocol, software, library, or other means for the creation of 3D PDFs or model files.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies showed that 3D PDF is a good means to help students understand anatomy [ 2 , 27 , 42 , 198 ] or surgical procedures [ 199 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difficulty of obtaining and maintaining corpses has been considered a major challenge, particularly in low-resource settings. Meanwhile, 3D printing technologies gain more widespread popularity due to decreasing costs and more user-friendly handling [ 1 ]. The ability to combine multiple materials within a single 3D-printed model allows for an accurate and patient-specific reconstruction of the pathology and provides an opportunity to simulate and compare surgical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…surgical corridors and focal neurologic deficits. This is mainly achieved through tangible 3D models [ 1 ]. Cadavers remain the gold standard for hands-on neuroanatomy education.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of intrinsic motivated students are selfcontrol, satisfaction, and joy from learning process 8 . Prior research has shown that motivation has a considerable effect on medical students' academic success [9][10][11] . The bulk of these studies, however, have focused on general motivation rather than specific motivating aspects.…”
Section: Introductionmentioning
confidence: 99%